Integrated management of chickpea and lentil viruses and their vectors in North Shewa, Ethiopia - Eshete, Beyene Bitew; Tewolde, Fekadu; Ali, Bereket; Belete, Aleme; Fantaye, Alemenew; Worku, Yifru; Kumari, Safaa; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2023)
Lentil and chickpea are the most important cool season legume crops grown in cereal based cropping system in the mid highlands central Ethiopia. Productivity of both crops is affected by several biotic factors such as pod borers, aphids, wilt/root rot, foliar diseases, and viruses. Most plant viruses are transmitted by many aphid species and thus management of insect vectors is one of the main options for controlling viral diseases. On-farm trials were conducted at Enewary, North Shewa in 2022 main cropping season to identify best options for the management of emerging lentil and chickpea virus diseases and their aphid vectors. One lentil (Derso) and one chickpea (Mastewal) varieties, two insecticides [Dimethoate (Dimeto 40% E.C) and Selecron 720 EC (a.i. 720g/L PROFENOPHOS)] sprayed three times during the season, and four sowing dates were used as treatments. Field observations during the growing season showed that reddening and yellowing were the major virus symptoms recorded on lentil whereas reddening virus symptoms was recorded on chickpea. Spraying insecticides significantly minimized aphid populations and reduced virus symptoms incidence in lentil. Highest lentil biomass and grain yield was recorded for early sowing date combined with insecticide sprays. The results obtained indicated that the management of viruses and aphid vectors can be achieved through adjusting sowing date for lentil and chickpea crops.